PENGARUH KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI INOVATOR DAN SUPERVISOR TERHADAP KINERJA GURU PADA SMP NEGERI 4 SIGI DI SMP NEGERI 11 SIGI - Musra, Musra (Katalogis, 2017)
The principal's role as an innovator and a supervisor is very important to improve the performance of teachers in Sigi. This type of research is quantitative research with correlation approach. Samples were teachers at SMPN 4 Sigi and SMPN 11 Sigi. The technique used is the study population because all the population sampled. This research data collection via questionnaires innovators, supervisor and teacher performance. Data analysis using SPSS 16 computer facilities. The results showed (1) There is a positive and significant impact of school leadership as an innovator on teacher performance of 57.60% in SMP Negeri 4 Sigi, and amounted to 18.50% in SMP Negeri 11 Sigi. (2) There is a positive and significant impact of school leadership as a supervisor on teacher performance of 34.30% in SMP Negeri 4 Sigi, and amounted to 11.10% in SMP Negeri 11 Sigi. (3) There is a positive and significant impact of school leadership as an innovator and supervisor of teachers on teacher performance of 64.80% in SMP Negeri 4 Sigi, and amounted to 18.70% in SMP Negeri 11 Sigi. This positive effect means that if the school leadership as an innovator and supervisors better then the teacher's performance increases.